Changes in UV-visible transmittance of silicone-hydrogel contact lenses induced by wear - Lira, Madalena (2009)
Purpose: To evaluate the influence of wear of silicone-hydrogel contact lenses on lens ultraviolet and visible spectrum transmittance by studying several contact lenses before and after wear. Methods: To investigate the ability of contact lenses to maintain their transmittance characteristics, we measured 104 different contact lenses in the ultraviolet (UV) and visible range from 200 to 700 nm, with a Shimadzu UV3101-PC UV-vis-NIR spectrophotometer equipped with an integrating sphere. The lenses used in this study were Acuvue Advance (Johnson & Johnson Vision Care, Inc.), Air Optix Night & Day (CIBA Vision), Air Optix (CIBA Vision), and PureVision (Bausch & Lomb). A conventional hydrogel contact lens was also tested, Acuvue (Johnson & Johnson Vision Care Inc.). Results: Our study indicates that lenses that do not have UV absorbers incorporated into the polymer transmitted most of the UV radiation (UVR) before and after wear. The results of the statistical analysis show that for the UVC portion of the spectrum significant difference exists within the measurements obtained before and after wear for all the lenses, with the exception of PureVision. Acuvue Advance is the only material in which significant transmittance differences were observed in the visible spectral range. Conclusions: Transmittance is modified after contact lenses wear, probably due to the formation of biofilms on the contact lens surface, being more noticeable in the UVR region of the spectrum (200–400 nm). Silicone-hydrogel and conventional hydrogel contact lens materials that provide UVR protection (UV-blocker) maintain this property even after being worn. The changes observed in the visible spectrum seem not to have any implications in visual performance of silicone-hydrogel contact lenses.